Investigation of state anxiety levels of parents admitted to the paediatric emergency department - Ahmet Yeşil; Ahmet Butun (BMC Pediatrics)
Abstract Introduction The psychological well-being of parents during their child’s emergency treatment can significantly influence the overall care experience and outcomes. Parental stress and anxiety may affect their ability to provide accurate information, make informed decisions, and support their child effectively during treatment. The aim of this study was to identify the levels of state anxiety experienced by parents whose children were receiving care in the Paediatric Emergency Department (PED), and related factors that contributing to parental anxiety. Methods This study is a descriptive cross-sectional study. The setting of the study was PED at a tertiary hospital with a 700-bed capacity. Participants were parents of children who visited the PED and received least urgent code during triage. The population of the study consists of a total of 426 parents of children admitted to the PED. Data were collected face-to-face between 4 November 2024 and 15 December 2024. Data collection tools included a socio-demographic questionnaire and the State-Trait Anxiety Inventory (STAI), a validated 40-item tool measuring state and trait anxiety. The data were analysed using SPSS Statistics for Windows. Results Majority of the visits were made by mothers (66%), while fathers were less active in this process (34%). The mean state anxiety score was 42.45 ± 8.94 and the mean trait anxiety score was 43.70 ± 8.12. Moreover, mothers exhibited significantly higher trait anxiety than fathers (p = 0,003). Significant differences were found in both state and trait anxiety scores according to mother’s education level (p < 0.001). It was found that the trait anxiety levels of non-employed mothers were significantly higher than those of employed mothers (p = 0.046). Anxiety levels were found to be higher in those who visited the PED more frequently. In addition, a significant difference was found in state anxiety scores according to the perceived urgency of the child’s condition, and it was observed that anxiety levels were higher in very urgent conditions (p < 0.001). Anxiety levels were significantly associated with maternal education (p < 0.001), non-employed status (p = 0.046), frequent PED visits, and perceived urgency of the child’s condition (p < 0.001). It was determined that those who were dissatisfied and those who were partially satisfied with the communication of healthcare staff had higher anxiety levels. It was seen that the anxiety levels of those who were dissatisfied and those who were partially satisfied with providing information by healthcare staff were higher (p = 0.020). The adequacy of allocated time for care made a significant difference in both state and trait anxiety scores, and it was observed that the anxiety levels of those who were dissatisfied and those who were partially satisfied with the adequacy of allocated time for care were higher. Dissatisfaction with staff communication and allocated care time also correlated with higher anxiety (p < 0.05). Conclusion Effectiveness of healthcare staff, the importance of communication, and the perceived quality of care provided to children in the PED were important indicators for parental anxiety. Effective communication between healthcare providers and parents could lead to increased level of parental satisfaction with healthcare staff and with the PED settings. Effective communication could reduce parental anxiety during the course of care and treatment, and thus enhancing the overall experience of families in the PED settings.